Some data on status of the herd of horsehair crab (Erimacrus isenbeckii) in the northwestern Tatar Strait - A. V. Kharitonov; P. A. Dulenina (Известия ТИНРО, 2023)
The data of trap surveys and observations aboard fishing vessels conducted in the northwestern Tatar Strait (northward from Cape Zolotoy) in 2009–2022 are analyzed. Horsehair crabs dwell along the entire continental coast from Cape Zolotoy in the south to Cape Nakatov in the north, but commercial aggregations with the density on average 232 ind./km2 are concentrated in the southern part of this area (south of 49о N). Seasonal bathymetric migrations of the crab include the fall moving of commercial males from the depths of 10–40 m to the depths of 40–60 m for wintering and their return to shallows in spring. Two dense wintering aggregations are formed usually between Cape Peschany – Cape Mapatsa and southward from 48о00′ N, whereas sparse summer aggregations are widely distributed along the coast. Regardless the season, the aggregations density decreases from south to north. The males are generally larger in the southern aggregations than in the northern ones (on average, 100.3 and 89.8 mm of carapace width, respectively), the difference is statistically significant (p < 0.0001). The stock of horsehair crab in the northwestern Tatar Strait has increased in the last 20 years from136 tons in 2003 to 1580 tons in 2022. Over the past 10 years, the optimal allowable catch in the Primorye subzone north of Cape Zolotoy was utilized less than 50 %. There is no specialized fishery of horsehair crab; the species is caught mainly as bycatch for other shelf crab species. High current level of the stock gives a good background for commercial removal of at least 158 t of horsehair crab without damage to the local population of this species.